REOG AS MEANS OF STUDENTS’ APPRECIATION AND CREATION IN ARTS AND CULTURE BASED ON THE LOCAL WISDOM - Ambarwangi, Sri; Suharto, Suharto (Harmonia: Journal of Arts Research and Education, 2014)
This paper is the result of the study and the implementation of learning in the field of the author, especially in the implementation of the study of Arts and Culture in the vocational schools. Thepurpose of this paper is to show that by learning local culture based on learning objectives the corresponding to the curriculum can be reached. In fact, the local culture also containing more local wisdom is felt directly by the students. The art of Reog, known around Pringapus Semarang Regency, can be used as a means of learning arts for students, especially in the activities of appreciation and expressions. The existing values in the art of Reog can be conceptually presented in class, as well as directly through the students’ activities of appreciation and expression in theform of performances in the school environment. Students can easily receive learning materials and can be more expressive while presenting the show. The values that are in the presentation of the art of Reog are social, religion, nationalism, and culture. Students can present Reog with enthusiasm and expressive as a show that has already exist for a long time in the environment of their own, and even many have become the performers of Reog in their neighborhood. Reog has already been part of his life that has the role of self-actualization, expression, social, and cultural. Most of those students feel proud to be a part in the show in his living quarters so that they do not feel ashamed of serving the art in school.